KEBIJAKAN KEPENDUDUKAN DI KABUPATEN SLEMAN PASCA BERAKHIRNYA MDGs - Beti Nur Hayati; Muhammad Arif fahrudin Alfana (NATAPRAJA, 2016)
The purpose of this study was to describe the specifics of population policy in Sleman post-MDGs. The issues are limited to a few indicators of education, health and poverty reduction. This research is a survey with key data used comes from Bappeda publication, the Central Bureau of Statistics, BKBPMPP and Dukcapil Sleman. The results showed that the achievement indikators of education, health and poverty reduction showed improvement from year to year. In 2015, most of these indikators have succeeded in meeting the targets set by the MDGs. In the future, education, health and poverty reduction still remains a strategic issue in the population development in Sleman. Some policies crafted to ensure that the development of population becomes better. Some of these policies are contained in the main points of development to create quality education, the creation of a healthy life and to realize a prosperous society and without poverty.Keywords: population policy, the subject of development, Sleman Regency